Kekuatan Otot Ekstremitas Bawah Memiliki Pengaruh yang Signifikan terhadap Keseimbangan Dinamis pada Surfers di Pantai Labu - Muliati, Muliati; Napitu, Marolop Parlindungan; Ginting, Isaharpika Br; Arianti, Melda Putri (Jurnal Riset Hesti Medan, 2024)
Surfing is one of the popular water sports that are popular in Bali, especially in Badung beach such as Kuta beach, Double six beach, Legian beach, and Uluwatu beach. People who played surfing called surfer and ride a surfboard, do manuever in order to stand and control the surfboard on the waves. Surfers need lower extremity muscle strength to maintain body balance on the surfboard. This is necessary to avoid the risk of injury of the body. This study aims to find out the relationship between lower extremity muscle strength and dynamic balance in surf players at Badung Beach. Study was analyzed by cross sectional analysis with the surfer population on Badung beach. A total of 35 samples were obtained to meet the inclusion riteris and exclusion criteria. The data was taken from the population on Kuta, Double Six, Legian, and Uluwatu beaches from July to September 2021 with a prepared formulir. The form consists of sample identity, measurement of lower extremity muscle strength with leg dynamometer and dynamic balance measurement with Y-Balance Test. This study showed the results of 35 samples that have been analyzed in surfers on Badung beach there is a relationship between lower extremity muscle strength and dynamic balance in surfers at Badung Beach with a P-value is 0.004. This study showed the relationship between lower extremity muscle strength and dynamic balance in surfers on Pantai Labu beach.